2023
DOI: 10.3390/medicina59030537
|View full text |Cite
|
Sign up to set email alerts
|

REST/NRSF Silencing Modifies Neuronal Gene Expression in siRNA-Treated HeLa Cells: A Preliminary Exploration in the Search for Neuronal Biomarkers of Cervical Cancer

Abstract: Background and Objectives: REST (RE1-silencing transcription factor) diminution is associated with transcriptional relaxation, neuropeptide overexpression, and phenotype redefinition in neuroendocrine cancers, but this effect has barely been studied in cervical cancer (CC). We previously reported reduced expressions of REST in samples with premalignant lesions and CC; however, the transcriptional consequences for neural genes associated with reduced REST expression in CC are unknown. Therefore, the objective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Furthermore, altered REST splicing was also found to mediate the anti-tumor effects of SRRM4 targeting in prostate cancer cells [246]. A recent study revealed REST diminution in premalignant lesions, squamous cell carcinoma (SCC), endocervical adenocarcinoma (ADC), and the cancerous cell lines SiHa and HeLa [262]. These investigations suggest that REST may be a hub that extensively regulates tumor occurrence and development and can serve as a diagnostic and therapeutic target.…”
Section: Non-nervous System Cancermentioning
confidence: 88%
“…Furthermore, altered REST splicing was also found to mediate the anti-tumor effects of SRRM4 targeting in prostate cancer cells [246]. A recent study revealed REST diminution in premalignant lesions, squamous cell carcinoma (SCC), endocervical adenocarcinoma (ADC), and the cancerous cell lines SiHa and HeLa [262]. These investigations suggest that REST may be a hub that extensively regulates tumor occurrence and development and can serve as a diagnostic and therapeutic target.…”
Section: Non-nervous System Cancermentioning
confidence: 88%